Ketahanan Ekonomi dan Peacebuilding: Pemberdayaan UMKM OTOP di Kawasan Konflik Thailand Selatan - Murokib Kode (Jurnal Ekonomi Bisnis dan Manajemen, 2026)
The southern border region of Thailand (Pattani, Yala, and Narathiwat) endures protracted conflict and structural poverty that constrain the economic activities of Malay-Muslim communities. This study analyzes the implementation of the One Tambon One Product (OTOP) program in a conflict zone, identifies the barriers and adaptation mechanisms of entrepreneurs, and evaluates the potential of OTOP as an instrument of economic peacebuilding. A sequential explanatory mixed-methods design was used: a survey of 150 OTOP entrepreneurs (stratified random sampling) and in-depth interviews with 18 informants (purposive sampling), analyzed through descriptive-inferential statistics and thematic analysis. Findings reveal that conflict affects six business dimensions: restricted mobility (73.3%), low trust in government programs (38.7%), difficult access to capital (68%), limited market penetration beyond the region (22%), low e-commerce adoption (29.3%), and psychosocial burden (61.3%). Communities developed four social-capital-based adaptation mechanisms: solidarity networks, mosque-based economic clusters, halal and Malay-Islamic identity specialization, and cross-border market linkages with Malaysia. The study contributes theoretically by integrating conflict-sensitive development, empowerment, and economic peacebuilding into a single analytical framework, and practically by recommending a conflict-sensitive OTOP program design through strengthened Islamic financing and cross-border trade corridors.